Sustainability, Diversity, and Equality: Key Challenges for Japan - Tanaka, Kimiko; Selin, Helaine (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book enables readers to understand contemporary Japanese society and culture. Since it is written by experts, it allows readers to start with any chapters they are interested in. It also provides a unique way to introduce Japanese society and culture to those who have never visited or studied Japanese society by reading articles from various authors on topics such as gender, family, economy, natural disasters and politics and laws. It provides scholars, academics, graduate students and the general educated audience all the information required to understand contemporary Japanese society and culture fully and see the diverse perspectives available.
Part 1. Beyond Numbers: Japan's Demographic Challenges and Future -- 1. Single and Unready to Mingle: The Insecure Lifeworlds of Never-Married Japanese (Akiko Yoshida and Caitlin Meagher) -- 2. Infertility in Relation to Japanese Prenatal Norms (Chiaki Shirai) -- 3. Patriarchy, Paternalism, and Politics of Reproductive Autonomy: Abortion Rights in Japan (Eiko Saeki) -- 4. Aging, Health, and Gender (Yuka Minagawa) -- 5. A Chronology of the COVID-19 Pandemic in Japan (Takeshi Yoda) -- 6. Hikikomori and Belonging in a Post-Pandemic Japan (Naomi Berman) -- 7. Migrant Long-Term Care Workers in Japan (Rie Miyazaki) -- 8. Will Guestworkers Save Japan? Findings from a Nationwide Municipal Survey (Yunchen Tian) -- 9. Precarity and Hope Among Asylum Seekers in Japan (Taku Suzuki) -- 10. Japanese Society in the Eyes of Immigrant Families: Focus on the Survival Strategy of Filipino Single Mothers (Sachi Takahata and Frieda Joy Angelica Olay Ruiz) -- 11. Depopulation (Susanne Klien) -- 12. Rural In-Migrants: Embracing Sustainable Lifestyles for a Post-Growth Society? (Simona Zollet) -- 13. A Regional Revitalization Strategy for Areas with Declining Populations: Transforming Tourists Into Local Actors (Hiroki Tahara) -- 14. Creating a Sustainable Society Beyond Times of Crisis (Hiroki Nakamura) -- 15. Displacement and Return: University Campuses as Ba and Ibasho for Sustainability Co-creation. (Peter Hourdequin) -- Part 2. The Myth of Homogeneity: Ignorance, Discrimination, and Prejudice Towards Soto -- 16. Education, Cultural Capital, and Social Class Reproduction (Yoko Yamamoto) -- 17. Buraku Issues: Changes and Challenges (Christopher Bondy) -- 18. Toward "No Homeless" Public Spaces? Homeless Policy and a Crisis of Japanese Urban Society (Mahito Hayashi) -- 19. Kodomo Shokudo (Children's Cafeterias): Changing Families and Social Inequality in Japan (Junko Nanahoshi) -- 20. Reimagining Japan Through the Experiences of Mixed Japanese (Yuna Sato, Yu-Anis Aruga, and Sayaka Osanami Törngren) -- 21. Redefining Japaneseness: Blackness, Whiteness, and the Discordant Discourse of Diversity in Japan (John G. Russell) -- 22. Questioning Xenophobia in Japan: Racism, Decolonization, and Human Rights (Sara Park) -- 23. Life Stories, Historical Background, and Current Situations of the Ainu: The Story of Noto (Vince Okada) -- Part 3. Gender Inequality: Challenging Gender Roles and the Gender Binary -- 24. Japan's Gender Inequality in Economics and Politics Since 1945 and the Policies That Engineered it (Emma Dalton) -- 25. Japan's Glass Ceiling: Contradictions in Gender Discourse and Institutional Support for Ie (Family) (Robert C. Marshall) -- 26. Surnames and Gender in Japan (Hiromi Taniguchi and Gayle Kaufman) -- 27. Family, Graves, and Gender in Japan (Kimiko Tanaka) -- 28. Male Caregivers in Japan: Between Care and Masculinity (Mao Saito) -- 29. LGBTQ Activism in Contemporary Japan: Prospects and Perspectives (Patrick Carland) -- 30. Nationalism and Queer Politics in Postwar Japan (Kazuyoshi Kawasaka).
Keywords: Philosophy, Japanese; Ethnology; Culture; Japan -- History; Japanese Philosophy; Regional Cultural Studies; History of Japan